Conceptual foundations for understanding smart tourism ecosystems. (September 2015) - Gretzel, Ulrike; Werthner, Hannes; Koo, Chulmo; Lamsfus, Carlos
Abstract: Using digital ecosystems and smart business networks as conceptual building blocks, this paper defines, describes and illustrates the idea of a smart tourism ecosystem (STE). It further draws on conceptualizations of smart technologies, smart cities and smart tourism to envision new ways in which value is created, exchanged and consumed in the STE. Technologies essential to the functioning of an STE are described and it is argued that data emerging from these technologies are the driver for new business models, interaction paradigms and even new species. Critical questions regarding the need for regulatory intervention and innovative research are raised.